Еще раз о Мережковских и Льве Толстом - Sobolev, Aleksandr; Sobolev, Lev (Wiener Slawistischer Almanach, 2024)
The article brings together different genres of evidence about Leo Tolstoy’s biographical contacts with the writing couple Zinaida Gippius and Dmitry Merezhkovsky. For the first time their surviving correspondence is printed in full. The only face-to-face meeting on May 11–12, 1904 is timed according to the sources. The immediate context of this meeting is described.